Marine heatwaves in shallow coastal ecosystems are coupled with the atmosphere: Insights from half a century of daily in situ temperature records - Cook, Felix; Smith, Robert O.; Roughan, Moninya; Cullen, Nicolas J.; Shears, Nick; Bowen, Melissa (Frontiers in Climate, 2022)
Marine heatwaves (MHWs) are extreme ocean temperature events that can have wide-ranging and pervasive effects on marine species and ecosystems. However, studies of MHW characteristics and drivers primarily focus on open-ocean environments, rather than the nearshore coastal ocean (<10 km from coast, <50 m depth). This is despite coastal waters sustaining significant commercial, recreational, and customary fisheries and aquaculture activities that are highly susceptible to the impacts of MHWs. The two longest (>50 year) daily in situ ocean temperature records in the Southern Hemisphere are used to investigate the variability, drivers and trends of MHWs in shallow water marine ecosystems (SWMEs). Located at the northern and southern limits of New Zealand, both locations experience an average of two to three MHWs annually, with MHWs at the exposed coastline site generally being of longer duration but less intense than those observed within the semi-enclosed harbour site. Observed MHWs have timescales similar to synoptic weather systems (8-12 days) and are most intense during Austral summer with little seasonality in frequency or duration. An investigation of MHWs co-occurring in nearshore coastal and offshore waters suggests that MHWs in semi-enclosed waters (e.g. harbours, estuaries) are more closely coupled with local atmospheric conditions and less likely to have a co-occurring offshore MHW than those occurring on exposed coastlines. Composite analysis using a reanalysis product elucidates specific atmospheric drivers and suggests that atmospheric pressure systems, wind speed and latent heat fluxes are important contributing factors to the generation and decline of MHWs in SWMEs. Investigation of long-term trends in MHW properties revealed an increase in MHW duration and annual MHW days at the southern site and decrease in maximum intensity at the northern site. This is consistent with broad-scale warming trends previously documented at these coastal stations, with differences related to changes in large-scale circulation patterns around New Zealand. Our results highlight the importance of in situ data for the analysis of MHW events in the nearshore coastal ocean, and the role of local atmospheric forcing in modulating the occurrence of MHWs in SWMEs, which can cause decoupling of temperature dynamics with the surrounding shelf sea.